Reaching hidden youth in Singapore through the Hidden Youth Intervention Program: A biopsychosocial approach integrating mental health and social work interventions - Khiatani, Sonia; Liu, Denise; Yeo, Benjamin Sen Son; Wong, John Chee Meng (Frontiers in Psychiatry, 2023)
Hidden youth are youth who withdraw from society for at least six months, physically isolating within their homes or rooms. There has been a steady rise in this phenomenon across many developed countries, and this trend is expected to continue. As hidden youths often present with complex psychopathology and psychosocial issues, multi-factorial intervention approaches are recommended. To reach this isolated population and address gaps in services, a community mental health service and a youth social work team collaborated to develop the first specialized intervention for hidden youth in Singapore. This pilot intervention combines components from Hikikomori treatment models from Japan and Hong Kong, and a treatment program for isolated individuals diagnosed with Internet Gaming Disorder. This paper describes the development of the pilot intervention model- a four-stage biopsychosocial intervention targeting the complex needs of hidden youth and their families- and illustrates its implementation and challenges faced through a case study. Based on two years of service delivery to 25 youths, good practices such as utilizing novel outreach strategies and the importance of involving and caring for caregivers are also highlighted. Preliminary outcomes of this ongoing pilot intervention indicate reductions in social withdrawal behavior and increased engagement in school or work, especially for youth at the final stage of intervention. Strengths of the program include its multi-disciplinary and flexible nature, and the whole-family approach. Limitations of this program included a lack of information on Singaporean hidden youth and the lack of quantitative outcome data of this pilot program. In future, we aim to further enhance program elements through collaboration with international and local partners, and to develop an evaluative framework to determine program effectiveness.